Cr-promoted formation of B2+L21 composite nanoprecipitates and enhanced mechanical properties in ferritic alloy. (15th January 2023) - Zhang, Lin; Wen, Yuren; Liu, Ye; Quan, Fangkai; Han, Jiajia; Yang, Simin; Chen, Xu; He, Shuang; Gorbatov, Oleg I.; Chen, Xiaowei; Wang, Shengxi; Qu, Xuanhui
Abstract: The critical role of Cr on nanoprecipitates and the mechanical property of Fe-Ni-Al-Mn ferritic steel were systematically studied in this research. The two types of nanoprecipitates in the Cr added alloy were characterized through a combination of aberration-corrected scanning transmission electron microscopy and atom probe tomography techniques. The atomic-scale structure and chemistry analysis reveal that fine globular-shaped precipitates have a B2-structure, while coarse elongated precipitates have B2+L21 composite structures. The first-principles calculations reveal that the segregation of Cr at the L21 /bcc interface reduces the interface and strain energy for the nucleation of the L21 -type phase. With the increasing precipitate size, the B2 structure is gradually transformed to L21 to reduce elastic strain, thereby promoting the formation of B2+L21 composite nanoprecipitate. The addition of 10 wt% Cr results in an increase of ∼275 MPa in yield strength without obvious loss of ductility. The effect of Cr on the strength mechanisms were quantitatively analyzed, revealing that the strength of the ferritic alloy mainly improved by the formation of B2+L21 composite nanoprecipitate, which is more effective than solid solution strengthening. Graphical abstract: Image, graphical abstract